Peran Perfeksionisme Orientasi Diri dalam Memediasi Pengaruh Gaya Pengasuhan Orang Tua terhadap Efikasi Diri Keputusan Karier Siswa - Annisa Nurul Utami; Puji Lestari Suharso; Rose Mini Agoes Salim (Universitas Negeri Surabaya, 2019)
This present study aimed to analyze the role of self-oriented perfectionism in mediating the effect of fathers and mothers parenting styles on Career Decision Self-Efficacy (CDSE) among students in Grade 11 Senior High School. The participants of the study comprised 179 students who were selected through convenience sampling method. This study employed three instruments, namely Career Decision Self-Efficacy Short Form, Parental Authority Questionnaire, and Multidimensional Perfectionism Scale. Data were analyzed by Hayess PROCESS Macro. Generally, the results show that fathers permissive parenting and mothers authoritarian parenting have an influence on the degree of CDSE among students which is mediated by self-oriented perfectionism. Moreover, the effect of fathers authoritative parenting predicts CDSE directly without the mediation effect of self-oriented perfectionism, whilst mothers authoritative parenting influences CDSE both directly and indirectly. Therefore, considering the actualization of proper parenting styles is necessary in order to build perfectionism personality which supports students effectiveness in career decision making.Keywords: Career decision self-efficacy, parenting styles, self-oriented perfectionism, studentsAbstrak: Penelitian ini bertujuan untuk menganalisis peran perfeksionisme orientasi diri dalam memediasi pengaruh gaya pengasuhan ayah dan ibu terhadap Efikasi Keputusan Diri Keputusan Karir (Career Decision Self-Efficacy/CDSE) siswa kelas XI SMA. Sebanyak 178 partisipan terkumpul melalui teknik convenience sampling dalam pengisian tiga macam skala, yaitu Career Decision Self-Efficacy Short Form, Parental Authority Questionnaire, dan Multidimensional Perfectionism Scale yang sudah dilakukan adaptasi ke dalam Bahasa Indonesia. Data dianalisis dengan menggunakan PROCESS Macro dari Hayes. Secara umum, hasil uji menemukan bahwa gaya pengasuhan permisif ayah dan gaya pengasuhan otoriter ibu berpengaruh terhadap tingkat CDSE siswa melalui perfeksionisme orientasi diri. Sementara itu, pengaruh dari gaya pengasuhan otoritatif ayah terhadap tingkat CDSE siswa hanya terjadi secara langsung. Adapun pengaruh dari gaya pengasuhan otoritatif ibu terhadap tingkat CDSE siswa dapat terjadi baik secara langsung atau tidak langsung melalui mediasi perfeksionisme orientasi diri. Untuk itu, dengan penerapan gaya pengasuhan yang tepat, perkembangan pribadi perfeksionisme siswa dapat mendukung kenaikan efektivitas keputusan karier masa depan.